A “New Normal” During Covid-19 Pandemic Lockdown: The Effectiveness of Work from Home among Malaysian Parents - Md Zain, Noor Nasyikin; Ibrahim, Noor Ayuernie; Tamsir, Fazilah; Poniran, Halimi; Abdul Rahman, Asma Rina; Abu Basar, Suria (Advances in Humanities and Contemporary Studies, 2022)
COVID-19 and the associated lockdowns meant many working parents were faced with doing work and family care at home simultaneously. To investigate the effectiveness of work from home (WFH) during lockdown, this study draws a subsample of working parents in Shah Alam (n = 362) conducted during lockdown in March 2020. Overall, majority of the respondents highly agreed that WFH is effective for them especially it gives the opportunities for the parents to flexibly manage their work, house chores, and kids. Contrary, this study reveals that mother and those who are self-employed are perceived that they are less effective in their work at home. Further, this study discovers that time flexibility and technology availability are positively influence WFH effectiveness. This signifies that the ability to control working time and the availability of ICT as well as technology tools helps for better balancing work with family life, which finally makes the work effective. These results are consistent with the Work-Family Border Theory and Work Resources Theory that argued time flexibility and technology availability granted for employees helps them in work-family balance and thereby enhance their work effectiveness. This study is significant to the office management in assessing the implementation of WFH platform as well in designing WFH standard operating procedure to ensure that working parents can work from home during the emergency state without compromise the work quality.